Synthesis of New 2,4-Disubstituted 2,3-Dihydrobenzo[g]indol-5-ones by an SRN1 Strategy - Biyogo, Alex Meye; Khoumeri, Omar; Terme, Thierry; Curti, Christophe; Vanelle, Patrice (Synthesis, 2015)
An original and short synthesis of substituted 2,3-dihydrobenzo[g]indol-5-ones by SRN1-mediated synthesis of 2-nitroalkyl-substituted naphthalene-1,4-diones followed by a one-pot reduction–cyclization reaction is reported.
Keywords: quinones; electron transfer; cyclization; heterocycles; 2,3-dihydrobenzo[g]indol-5-one